Waters quality test based on macrozoobenthos bioindicator parameter in the Bolong river, Magelang - Setiyo Prajoko; Karunia Galih Permadani; Ivana Riqoh; Faiqoh Faiqoh (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2021)
The exploration of macrozoobenthos diversity as a bioindicator parameter in the Bolong river, Magelang has not been widely carried out. This study aims to determine the water quality of the Bolong river based on macrozoobenthos Bioindicator parameters. This research method uses a qualitative descriptive approach. The water quality test is measured based on the level of macrozoobenthos diversity according to the Shannon-Wienner diversity index. The purposive sampling method is used to determine 5 stations for sample collection. The intake of macrozoobenthos is done by using a Surber net and a tray at the bottom of river waters. Moreover, sampling is carried out with three repetitions. The data is analyzed using a diversity index, uniformity index, and dominance index to determine the water quality based on the Bioindicator parameters. Based on the result of the study, the macrozoobenthos diversity index is 1.028. Based on this index, the quality of waters in the Bolong river is considered as moderate pollution.